Area fluxes of carbon dioxide, methane, and carbon monoxide derived from airborne measurements around Greater London: A case study during summer 2012. Issue 8 (24th April 2014) - O'Shea, Sebastian J.; Allen, Grant; Fleming, Zoë L.; Bauguitte, Stephane J.‐B.; Percival, Carl J.; Gallagher, Martin W.; Lee, James; Helfter, Carole; Nemitz, Eiko
Abstract Airborne measurements of thermodynamic properties and carbon dioxide (CO2), methane (CH4), and carbon monoxide (CO) mole fractions were recorded on board the FAAM BAe‐146 UK research aircraft and used to characterize the inflow and outflow from Greater London on 30 July 2012. All three trace gases were observed to be significantly enhanced downwind of Greater London with spatially resolved plumes of comparable extent and position. A mass budget calculation using a box model approach (and uncertainty propagation) was used to determine net regional fluxes of 21 ± 3 µmol CO2 m−2 s−1, 0.13 ± 0.02 µmol CH4 m−2 s−1, and 0.12 ± 0.02 µmol CO m−2 s−1 for Greater London. These fluxes are comparable with simultaneous surface observations and previous studies in urban environments. A comparison was made with the 2010 UK National Atmospheric Emissions Inventory (NAEI), and fluxes from this study are found to be factors 2.3 for CO2 and 2.2 for CO larger than those estimated by the spatially disaggregated NAEI (2011) for Greater London. Fluxes of CH4 were found to be a factor 3.4 larger than the UK NAEI (2009). The efficacy of this mass balance approach, in general, is also discussed in terms of key assumptions and uncertainties, and we offer advice for future studies on how uncertainties could be reduced.